2016
DOI: 10.1159/000446286
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Brain-Derived Neurotrophic Factor and Psychopathology in Attempted Suicide

Abstract: Background/Aims: Increasing evidence suggests a link between brain-derived neurotrophic factor (BDNF) and suicidal behaviour (SB). Furthermore, decreased peripheral BDNF levels have been associated with clinical symptoms in various psychiatric disorders as well as with personality dimensions in healthy individuals. However, the relationship between BDNF and psychopathology is poorly investigated regarding SB. Methods: Plasma BDNF concentrations were analysed in 61 recent suicide attempters. Clinical symptoms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…BDNF rs6265 A allele and FGF21 rs11665896 T allele caused the production of mature protein (BNNF and FGF21) to decrease ( 30 , 38 ). In a sample of individuals who had attempted suicide ( 39 ) and in attention-deficit hyperactivity disorder patients ( 40 ), low blood BDNF concentrations were associated with high levels of impulsivity. Low FGF21 levels in the cerebrospinal fluid led to impulsivity ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…BDNF rs6265 A allele and FGF21 rs11665896 T allele caused the production of mature protein (BNNF and FGF21) to decrease ( 30 , 38 ). In a sample of individuals who had attempted suicide ( 39 ) and in attention-deficit hyperactivity disorder patients ( 40 ), low blood BDNF concentrations were associated with high levels of impulsivity. Low FGF21 levels in the cerebrospinal fluid led to impulsivity ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…It contains memories stored episodically, which means that they originate from different events, for example, from different times, places, associated emotions, and other conception-based knowledge (Conway & Bekerian, 1987). Suicidal individuals, especially, seem to have inaccurate autobiographical memories related to their use of maladaptive coping strategies (Pollock & Williams, 2004;Evans, Williams, Schotte & Clum, 1987;Linehan, et al, 1987;Orbach et al, 1990;Ambrus et al, 2016;Ambrus et al, 2020). People suffering from dementia have often lost their spatial orientation, but by focusing on specific activities related to places, their memories are activated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing individuals who have previously attempted suicide indicate both lower levels of serum and plasma BDNF compared to nonattempters [36][37][38][39]. However, a few studies have demonstrated no difference in serum BDNF levels between suicide attempters vs. non-attempters, nor correlations between plasma BDNF and clinical symptoms [40][41][42][43]. To date, the only study that examined BDNF and suicidality in SZ found no difference in serum BDNF levels between suicide attempters and non-attempters [44].…”
Section: Introductionmentioning
confidence: 99%